The IMPLEMENTATION OF COMBINATION OF COOPERATIVE LEARNING MODELS OF NUMBER HEAD TOGETHER AND SNOWBALL THROWING TYPES USING 3-DIMENSIONAL MEDIA TO IMPROVE STUDENTS' LEARNING OUTCOMES: PENERAPAN KOMBINASI MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBER HEAD TOGETHER DAN SNOWBALL THROWING BERBANTUAN MEDIA 3 DIMENSI UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Hana, Ngguna Wori; Bano, Vidriana Oktoviana; Ndjoeroemana, Yohana (Universitas Cokroaminoto Palopo, 2025)
This study aims to improve student learning outcomes by implementing a combination of Number Head Together (NHT) and Snowball Throwing (ST) learning models assisted by 3D Media on the Human Reproductive System material. This type of research is classroom action research (CAR), with a quantitative descriptive approach. The subjects of this study were students of class XI IPA SMA Negeri 1 Paberiwai in the 2024/2025 academic year. Students' cognitive learning outcomes were measured using posttests in cycles I and II. The results of the study showed that the application of a combination of Number Head Together (NHT) and Snowball Throwing (ST) learning models assisted by 3D Media can improve student learning outcomes. Based on the results of the study, the percentage of student learning outcomes in the Precycle of students who completed 31%, in Cycle I 44% and Cycle II 89%. Affective learning outcomes In cycle I, the results obtained were low predicates of 6 students, medium predicates of 12 students, while the high category was 7 students. In cycle II the predicate 5 students in the medium category, and 20 students in the high category. The conclusion obtained from this study is that the application of a combination of Number Head Together (NHT) and Snowball Throwing (ST) learning models assisted by 3D Media can improve the learning outcomes of class X IPA students of SMA Negeri 1 Paberiwai.